HAYVONLARDA UCHRAYDIGAN PARAZITLAR VA ULARNING TURLARI (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
This chapter systematically analyzes the diversity of animal parasites, their biological characteristics, life cycles, and impact on host organisms. Primary focus is given to protozoa and helminths (particularly nematodes), elucidating their morphological, taxonomic, and pathogenic features. The study also examines parasite transmission mechanisms, epidemiological spread, and economic significance in livestock. Research findings discuss existing strategies for controlling parasitic diseases and provide recommendations for future research directions, especially within the context of Uzbekistan.